IL-6/STAT3 Induced Neuron Apoptosis in Hypoxia by Downregulating ATF6 Expression - Zhou, Simin; Zhong, Zhifeng; Huang, Pei; Xiang, Bin; Li, Xiaoxu; Dong, Huaping; Zhang, Gang; Wu, Yu; Li, Peng (Frontiers in Physiology, 2021)
Background: Neuron apoptosis, regulated by endoplasmic reticulum (ER) stress in the hippocampus, is an essential factor influencing the cognitive impairment induced by hypobaric hypoxia. Hypoxia mainly changes the activating transcription factor (ATF6) pathway of ER stress. However, the role of ATF6 in neuron survival, apoptosis, and upstream regulation is still controversial. Methods: We established a hypobaric hypoxia-induced C57BL/6 murine model and cell lines exposed to 1% hypoxia, including PC12 and HT22. First, we tested the expressions of interleukin 6 (IL-6), IL-1β, and IL-10 in C57BL/6 mice’s hippocampus under hypoxia using enzyme-linked immunosorbent assay (ELISA). We determined the signal transducer and activator of transcription 3 (STAT3) phosphorylation at tyrosine (Tyr)705 by western blot, and the expression of ATF6, 78-kDa glucose-regulated protein (GRP78), and C/-EBP homologous protein (CHOP) related to ER stress by immunofluorescence (IF), western blot, and qRT-PCR; they were then verified on the cell model. Additionally, IL-6 (40 ng/mL) and STAT3 siRNA were used to treat the PC12 cells for 48 h and 4 h, respectively. Subsequently, they were exposed to 1% hypoxia for 48 h to activate or silence STAT3. Furthermore, the ATF6 and CHOP expressions were detected with western blot and qRT-PCR. Finally, we examined the binding of STAT3 to the ATF6 promoter by chromatin immunoprecipitation (ChIP)-seq. Results: The results showed that IL-6 increased, IL-10 decreased in the hypoxia group, and IL-1β showed no difference between the hypoxia and the normoxia groups. Neuron apoptosis was significantly elevated by exposure to hypoxia for 48 h in PC12 cells. The hypobaric hypoxia-induced ER stress proteins, ATF6, GRP78, and CHOP, and the p-STAT3 (Tyr705) expressions increased both in in vivo and in vitro. Besides, STAT3 silencing significantly promoted the ATF6 expression and inhibited CHOP, while STAT3 activation downregulated the expression of ATF6 and upregulated CHOP in PC12 cells. The ChIP-seq assay demonstrated that p-STAT3 (Tyr705) protein could bind to the ATF6 promoter region in HT22 cells. Conclusion: Phosphorylation of STAT3 at the Tyr705 site contributes to hypoxia-induced neuron apoptosis by downregulating ATF6, which might explain the inflammatory reaction and apoptosis of the hippocampal neurons induced by ER stress.